Analysis of the implementation of Profil Pelajar Pancasila through school culture - Raymundus Eko; Deny Setiawan; Anita Yus (Inovasi Kurikulum, 2024)
Learning encourages paradigm changes, including those related to school curriculum and education. Therefore, it is essential to ensure teachers' understanding of Profil Pelajar Pancasila and how to implement it through school culture at UPT SPF SD Negeri 101799 Deli Tua. The research subjects were 16 teachers and 74 students. The research method used is descriptive qualitative research using observation, interview, and questionnaire data collection techniques. The research results show that the implementation of Profil Pelajar Pancasila at UPT SPF SD Negeri 101799 Deli Tua has gone very well. This excellent result is supported by the teacher's understanding of the concept of Profil Pelajar Pancasila. The implementation of this program is also supported by 8 (eight) school cultures, namely religious culture, 5S culture (Senyum. Sapa, Salam, Sopan, dan Santun), Flag Ceremony culture, I work alone culture, Nail Cutting culture, Clean Class culture, Literacy culture, and “I Can” culture. By implementing the Kurikulum Merdeka and these eight cultures, UPT SPF SD Negeri 101799 Deli Tua, as one of the driving schools, has made maximum efforts to realize students as lifelong learners with the character of the Profil Pelajar Pancasila. AbstrakPembelajaran mendorong terjadinya perubahan paradigma, termasuk yang berkaitan dengan kurikulum dan pendidikan di sekolah. Maka dari itu penting untuk memastikan pemahaman guru tentang Profil Pelajar Pancasila dan cara implementasinya melalui budaya sekolah di UPT SPF SD Negeri 101799 Deli Tua. Subjek penelitian adalah 16 orang guru dan 74 peserta didik. Metode penelitian yang digunakan adalah penelitian kualitatif deksriptif dengan teknik pengumpulan data observasi, wawancara dan angket. Hasil penelitian menunjukan bahwa implementasi Profil Pelajar Pancasila di UPT SPF SD Negeri 101799 Deli Tua telah berjalan dengan sangat baik. Hasil sangat baik ini didukung oleh pemahaman guru terhadap konsep Profil Pelajar Pancasila. Implementasi program ini juga didukung oleh 8 (delapan) budaya sekolah yakni budaya Religius, budaya 5S (Senyum. Sapa, Salam, Sopan, dan Santun), budaya Upacara Bendera, budaya Aku Kerja Sendiri, budaya Potong Kuku, budaya Bersih Kelas, budaya Literasi dan, budaya Aku Bisa. Dengan menerapkan Kurikulum Merdeka dan kedelapan budaya ini, UPT SPF SD Negeri 101799 Deli Tua sebagai salah satu Sekolah penggerak, telah berusaha secara maksimal dalam mewujudkan peserta didik sebagai pembelajar sepanjang hayat yang berkarakter Profil Pelajar Pancasila.Kata Kunci: Budaya Sekolah, Kurikulum Merdeka, Profil Pelajar Pancasila